ECONOMIC RELATIONS WITH THE NEIGHBORING REGIONS IN THE FIRST HALF OF THE XXth CENTURY IN CENTRAL ASIA (EXEMPLIFIED BY THE CITY OF KOKAND) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article is devoted to the role of Kokand in the economic life of Central Asia in the first half of the 19th century. Information is given about the trading markets of Kokand in the city, both for their own traders and for merchants from other regions who arrived in the city along caravan routes. The merchants of the Khanate conducted brisk trade with many neighboring and distant countries, such as Bukhara, Khiva, Iran, Afghanistan, China, India, Arabia, Turkey and others directly. And through Tashkent with Southern Kazakhstan and the Kyrgyz nomads. By the end of the 19th century, the city became a major hub in trade between Russia and the East. The export of raw materials and the import of finished products was established.